Kualiti Kehidupan Kerja Dan Kesetiaan Di Kalangan Pegawai Perkhidmatan Pendidikan - Rohayati, Abd. Hamed (1999)
This study attempts to explore the relationship of quality of work life (QWL) and organizational loyalty among teachers from secondary school in Hulu Langat district, Selangor. Studies in the West have shown that the QWL influences organizational loyalty. However, in Malaysia such specific study concerning teachers have not been conducted. The study further examined the perception towards QWL and organizational loyalty and the differences of organizational loyalty according to gender, age, income, service group, length of service and level of education. A survey questionnaire set was used to gather data among 320 teachers from secondary school in Hulu Langat, Selangor which consist of two measurement tools. QWL was measured using Walton’s (1973) criteria whilst organizational loyalty measures were constructed in Malaysian context from Organizational Commitment Questionnaire scale by Mowday et.al (1979) and Cook and Wall’s scale. The data were analyzed with t-test, ANOVA and Pearson correlation analysis using SPSS 7.5 package. Results from correlation analysis reveal that there is a very significant relationship with QWL and organizational loyalty among teachers from secondary school in Hulu Langat district, Selangor. The criterion of development of human capabilities shows the highest significant relationship between organizational loyalty, while the criterion of the overall well being shows the lowest significant relationship with organizational loyalty. t-test and ANOVA shows there are significant differences in organizational loyalty according to sex, age, income, service group and level of education, but there is no significant difference based on length of service.